IMPLEMENTASI MODEL PEMBELAJARAN QUANTUM TEACHING AND LEARNING PADA MATERI LISTRIK DINAMIS UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR SISWA MTs MUHAMMADIYAH JAYAPURA - Desvita Astari Djamion (Balai Diklat Keagamaan Papua, 2021)
ABSTRACT This study aimed to increase the interest and learning outcomes of class IX B students in Dynamic Electricity material through the application of the Quantum teaching and learning model. This research is action research. Based on observations, it turns out that student learning outcomes on dynamic electricity are quite satisfactory. The problem raised in this study is whether applying the Quantum teaching, and learning model can improve student learning outcomes of Islamic junior high school of Muhammadiyah Jayapura class IX B on Dynamic Electricity material. Based on the test results in Cycle I and Cycle II, the students' mastery percentage in the first cycle was 61.90%, and the second cycle was 85.71%. The average percentage on the interest observation sheet in the first cycle is 65.65%, and the second cycle is 77.62%. The observation sheets for Quantum teaching and learning in cycle I was 66.65%, and Cycle II was 79.98%. Thus, the study results through the application of the Quantum teaching and learning model in the science subjects of dynamic electricity material can increase the interest and learning outcomes of students of Islamic junior high school of Muhammadiyah Jayapura class IX B in the even semester in the academic year 2020/2021. Keywords: Dynamic Electricity, Learning Model, Quantum teaching and learning ABSTRAK Tujuan penelitian ini adalah untuk meningkatkan minat dan hasil belajar siswa kelas IX pada materi Listrik Dnamis melalui penerapan model pembelajaran Quantum teaching and learning. Penelitian ini merupakan penelitian tindakan (action research). Berdasarkan hasil pengamatan, ternyata hasil belajar siswa pada materi listrik dinamis cukup memuaskan. Permasalahan yang diangkat pada penelitian ini adalah Apakah penerapan model Quantum teaching and learning dapat meningkatkan hasil belajar siswa MTs Muhammadiyah Jayapura kelas IX pada materi Listrik Dinamis. Berdasarkan hasil test Siklus I dan Siklus II, maka presetase ketuntasan siswa pada siklus I adalah 61,90 % dan siklus II adalah 85,71 %. Rata-rata persentase pada lembar observasi minat siklus I adalah 65,65 % da siklus II adalah 77,62 %. Persentase lembar observasi tindakan Quantum teaching and learning Siklus I adalah 66,65 % dan siklus II adalah 79,98 %. Dengan demikian maka hasil penelitian melalui penerapan model pembelajaran Quantum teaching and learning pada mata pelajaran IPA materi listrik dinamis dapat meningkatkan minat dan hasil belajar siswa MTs Muhammadiyah Jayapura kelas IX semester genap tahun pelajaran 2020/2021. Kata kunci : Listrik Dinamis, Model Pembelajaran , Quantum teaching and learning